Iceberg production and characteristics around the Prince of Wales Icefield, Ellesmere Island, 1997-2015. Issue 1 (1st January 2019) - Dalton, Abigail; Copland, Luke; Tivy, Adrienne; Van Wychen, Wesley; Cook, Alison
ABSTRACT: Since the 1960s, warming air and sea surface temperatures have led to decreasing sea ice extent and longer periods of open water in the Canadian Arctic Archipelago (CAA), together with changes in glacier discharge patterns. An important question, therefore, is whether there is a relationship between changing sea ice conditions, glacier dynamics, and iceberg production in this region. Using synthetic aperture radar (SAR) (Radarsat-1, Radarsat-2, and ALOS PALSAR) and optical (Landsat 7 and 8) satellite imagery, iceberg plume events and sea ice break-up/freeze-up dates between 1997 and 2015 are investigated for 40 tidewater glaciers around the Prince of Wales (POW) Icefield, Ellesmere Island. Results show a clear relationship between the presence of sea ice and the production of icebergs, with 49% of total iceberg plume events occurring during the 3–4 month long summer open water season and 51% of events when sea ice was present the remaining 8–9 months of the year. There is no clear evidence of recent increases in iceberg production on a regional basis, but on a local, individual glacier scale there has been a connection between periods of increased iceberg plume events and: (a) acceleration in the surface velocity of Trinity and Wykeham glaciers; (b) increase in terminus retreat rates for glaciers which have not accelerated in flow speed over the past 5–10 years. Comparisons with ocean temperature, surface air temperature from NCEP-NCAR reanalysis, and tidal data showed no clear relationship with iceberg plume events.